Analysis of Students' Learning Motivation Using Guided Inquiry Learning Model - Monica Julia Sari; Paidi (Postgraduate, University of Mataram, 2023)
The implementation of this study aims to analyze students' learning motivation toward the application of the Guided Inquiry learning model at SMA Colombo Yogyakarta. The research design used in this research is experimental. The sample used in this study was class XI students with a total of 9 students, but learning activities were carried out in one class but focused on 9 students. The sampling technique used was purposive sampling. The data collection technique was carried out by filling in the student's learning motivation questionnaire. The data analysis used is a descriptive analysis by calculating the percentage of the overall score on the learning motivation questionnaire. The results of this study are the level of learning motivation of students at SMA Colombo Yogyakarta in the high category by filling out a questionnaire by 5 students and very high by filling out a questionnaire by 4 students. The role of the teacher in learning activities using the Guided Inquiry model has a very large role in developing students' learning motivation.